STUDI KASUS PENGARUH HIPNOTERAPI TERHADAP PENURUNAN PTSD (POST TRAUMATIC STRESS DISORDER) PADA REMAJA PEREMPUAN KORBAN KEKERASAN BERPACARAN - Siska Dwi Ningsih; Indo Mora; Sinarsi Meliala; Cahyaning Fitri (Psikologi Universitas Sari Mutiara Indonesia, 2021)
Teenagers who are dating go through a lot of anxiety, rashness, internal and external conflicts because they need to adapt to their physical and psychological adjustment problems. The consequences and impacts of adjustment problems in the adolescent phase will lead to violence in dating. Female victims who experience dating violence both physiologically and psychologically from their lover and then break the relationship, instead of getting peace they actually get post- violent trauma called PTSD (Post Traumatic Stress Disorder). This research is entitled “Case Study of the Effect of Hypnotherapy on the Reduction of PTSD (Post Traumatic Stress Disorder) in Adolescent Female Victims of Dating Violence” is aimed at seeing the effect of hypnotherapy on the reduction of PTSD (Post Traumatic Stress Disorder) in adolescent females who are victims of datting violence. The research design is mixed methods research (MMR) and is a pre-experimental design, one group pretest-posttest design. Subjects in this study amounted to 2 people as indicated PTSD and 1 subject as data triangulation. PTSD was revealed through the PTSD Scale with a total of 92 statements. The results showed that WA subject after being given the intervention decreased from the category of severe PTSD symptom degrees with a number of 245 to the category of mild PTSD symptom degrees with a score of 170. And AV subject after being given the intervention decreased from the category of mild PTSD symptom degrees with a number of 216 to the category of mild PTSD symptom degrees with a number of 158. The results of descriptive statistics on the pre-test with SD= 20,506 and the results on the post-test with SD= 8,485. This shows that hypnotherapy has been proven to reduce PTSD (Post Traumatic Stress Disorder) in adolescent girls who are victims of dating violence.